2014
DOI: 10.1007/s00220-014-2131-9
|View full text |Cite
|
Sign up to set email alerts
|

Critical Edge Behavior and the Bessel to Airy Transition in the Singularly Perturbed Laguerre Unitary Ensemble

Abstract: In this paper, we study the singularly perturbed Laguerre unitary ensemblewith V t (x) = x + t/x, x ∈ (0, +∞) and t > 0. Due to the effect of t/x for varying t, the eigenvalue correlation kernel has a new limit instead of the usual Bessel kernel at the hard edge 0. This limiting kernel involves ψ-functions associated with a special solution to a new thirdorder nonlinear differential equation, which is then shown equivalent to a particular Painlevé III equation. The transition of this limiting kernel to the Bes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 49 publications
(92 citation statements)
references
References 45 publications
3
89
0
Order By: Relevance
“…Chen and Its showed that this weight associated with a certain linear statistics model, and investigated the Hankel determinant and relevant statistic quantities, and these can be expressed in terms of a Painlevé III equation for finite n dimensional by the ladder operator technique, the Riemann–Hilbert formation of the orthogonal polynomials and the Jimbo–Miwa theory. Xu, Dai, and Zhao studied the limit behavior of the kernel, and it turns out to be a Painlevé III kernel, which can also translate to be the Bessel kernel and the Airy kernel with different conditions. The double scaling limit of the Hankel determinant is also associated with the Painlevé III equation, see .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen and Its showed that this weight associated with a certain linear statistics model, and investigated the Hankel determinant and relevant statistic quantities, and these can be expressed in terms of a Painlevé III equation for finite n dimensional by the ladder operator technique, the Riemann–Hilbert formation of the orthogonal polynomials and the Jimbo–Miwa theory. Xu, Dai, and Zhao studied the limit behavior of the kernel, and it turns out to be a Painlevé III kernel, which can also translate to be the Bessel kernel and the Airy kernel with different conditions. The double scaling limit of the Hankel determinant is also associated with the Painlevé III equation, see .…”
Section: Introductionmentioning
confidence: 99%
“…To study the asymptotic behaviors of orthogonal polynomials and the Hankel determinant associated with the Pollaczek–Jacobi type weight, we introduce a model Riemann–Hilbert problem (RHp for short) for Ψfalse(ξ,ςfalse),ς=2n2t, and its existence and uniqueness had been proved by Xu, Dai, and Zhao . Although its explicit solution of this model cannot write down for finite ς=2n2t,Ψfalse(ξ,ςfalse) can be approximated by the Bessel model RHp as ς0 and the Airy model RHp as ς, separately.…”
Section: Introductionmentioning
confidence: 99%
“…consider the asymptotics of the partition function associated with the Gaussian weight perturbed by an essential singularity and they get Painlevé III‐type asymptotics. In and , Xu et al. also obtain Painlevé III‐type asymptotics of the Hankel determinants associated with the Laguerre weight with an essential singularity at the hard edge.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 96%
“…In , asymptotic formulas have been derived of the Hankel determinants associated with the Jacobi weight perturbed by a Fisher–Hartwig singularity close to the hard edge x=1, involving the Jimbo–Miwa–Okamoto σ‐form of the Painlevé III equation. The Painlevé equations play an important role in the asymptotic study of the Hankel determinants; see , , , and .…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%